Influence of Patient’s Age and Gender on Dental Implant Treatment Five Year retrospective study - Alhamdani, Faaiz; Abdulla, Emad. Hammody. (Jour Med Resh and Health Sci, 2021)
Background: In developing countries, there is an increase in awareness among the population regarding dental implant treatment. However, there is paucity in studies on the relationship between patients’ biographic information, and different aspects of dental implant treatment. Aims: This study’s purpose is to determine the influence of Iraqi patients’ age and gender on various clinical aspects in dental implant treatment. Methods and Materials: Biographic data of 196 Iraqi patients who attended a private dental implant center in Baghdad from 7.1.2016 to 30.4.2020 was recorded. During this period 348 dental implant procedures were completed. The recorded data included: patient age, gender, implant zone, implant timing, implant side, dental implant system, sinus lift, bone augmentation, implant length, and implant diameter. SPSS Ver. 25 was used to perform the statistical analysis. Results: There was a highly significant negative relationship (p=0.006) between implant length and patient’s age, and a significant positive relationship (p=0.028) between implant size and patient’s age. A statistically significant relationship (p=0.013) was found between the patient’s age and dental implant zone and dental implant timing (p=0.016). A significant difference was found between the two genders in terms of dental implant timing (p=0.017). Conclusion: females are better candidates for dental implant treatment. Older patients seem to benefit more from shorter, and, subsequently, wider dental implants. Also, older patients tend to have lower anterior dental implants.